Features and Effects of Athlete Burnout Among Top Amateur Female Rugby Union Players - Martin, K.; Hong, H. J. (The Sport Psychologist, 2022)
This paper addresses the contributing factors and effects of athlete burnout in women`s rugby. Current and former top amateur female rugby union players (N?=?10, age 19-21 yr) were interviewed regarding their experiences of high-performance rugby and of athlete burnout. Thematic analysis was applied to analyze the data. The findings show that seven players exhibited the three dimensions of burnout: emotional and physical exhaustion, reduced sense of accomplishment, and sport devaluation. Significant antecedents included role conflict, high physical demands, and coaching behaviors that resulted in maladaptive outcomes. The findings were in line with self-determination theory and showed consistencies with previous literature regarding athlete burnout. Meaningful and original findings related to the female rugby setting were also presented and discussed. Therefore, the study provides new insights into female rugby players` experience of athlete burnout and contributes to the understanding of athlete burnout in the context of women`s rugby, which has been underresearched.